2011
DOI: 10.1016/j.exer.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TGFβ and PDGF-B blockade on corneal myofibroblast development in mice

Abstract: The purpose of this study was to investigate the role of transforming growth factor beta (TGFβ) and/or platelet-derived growth factor-B (PDGF-B) blockade on the differentiation of vimentin and alpha-smooth muscle actin (αSMA)-expressing myofibroblasts associated with haze in mice. Mouse corneas had haze-generating irregular PTK (phototherapeutic keratectomy) and topical treatment with the vectors. Six study groups of PTK treated corneas, with four corneas per group in each experiment, were Group 1) treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 24 publications
(48 reference statements)
1
61
0
8
Order By: Relevance
“…Furthermore, PDGF has been shown to induce myofibroblast activation in the eye directly or in synergy with TGF-β1 (Jester et al, 2002), also recently shown for bone-marrow derived precursors (Singh et al, 2014), which results the in loss of crystalline production in keratocytes (LaGier et al, 2013). Likewise, blocking PDGF action inhibits corneal myofibroblast activation (Kaur et al, 2009b;Singh et al, 2011).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
“…Furthermore, PDGF has been shown to induce myofibroblast activation in the eye directly or in synergy with TGF-β1 (Jester et al, 2002), also recently shown for bone-marrow derived precursors (Singh et al, 2014), which results the in loss of crystalline production in keratocytes (LaGier et al, 2013). Likewise, blocking PDGF action inhibits corneal myofibroblast activation (Kaur et al, 2009b;Singh et al, 2011).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
“…The development of myofibroblasts has been well characterized with in vitro models and in animal models following photorefractive keratotomy (PRK) (Jester et al, 1999c; Masur et al, 1996; Mohan et al, 2003; Mohan et al, 2008; Singh et al, 2011; Singh et al, 2014b). In vitro studies have demonstrated that TGFβ is a key cytokine in the development of corneal myofibroblasts (Jester et al, 1999a; Masur et al, 1996; Singh et al, 2014b).…”
Section: Corneal Opacity — Development Persistence and Regressionmentioning
confidence: 99%
“…Firstly, repair of corneal epithelial basement membrane and restoration of basement membrane barrier function lead to stromal withdrawal of epithelial-derived TGFb, and possibly other cytokines such as platelet-derived growth factor (PDGF), which are important for phenotype transformation and viability maintenance of myofibroblast, and in turn induce corneal myofibroblast apoptosis. 10,[27][28][29][30] Secondly, many cytokines including IL-1, TNFa, and platelet-activating factor (PAF) play active roles in the elimination of myofibroblasts by activating apoptosis related signaling pathway. 8,9 In this study, we used two different models of apoptosis, in which treatment with TNFa plus CHX or serum starvation was used, respectively, to imitate the in vivo condition that corneal myofibroblasts undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%